Volleyball in unsportsmanlike university: development trends - Nataliya Grutsyak (Kharkiv State Academy of Physical Culture, 2015)
Purpose: the development and the basing of organizational actions for the work of sports groups of volleyball in unsportsmanlike higher educational institutions. Material and Methods: analysis and synthesis of scientific literature; analysis of the educational process; pedagogical supervision. Results: a curricula and programs are developed and proved for the work of sports groups of volleyball in unsportsmanlike higher educational institutions, test standards and tests are offered and substantiated, the educational manual is created. Conclusions: it is expedient to organize classes on physical training in groups with sports orientation taking into account a desire and physical capacities of students in higher educational institutions of an unsportsmanlike profile that is leads to the increase of visit and activity on classes of students to the improvement of their physical fitness and physical development. The program of the specialization "Volleyball" can become a basis for the creation of the Typical program for unsportsmanlike higher educational institutions.